Implementation of Library Accreditation within the Ministry of Health - Chronika S, Jeni Helen; Bratakusuma, Deddy Supriadi; Rustanto, Agung Edi; Wicaksana, Harits Hijrah; Hidayat, Yahya Rachmana (Eduvest - Journal of Universal Studies, 2025)
The purpose of this study is to examine the implementation of library accreditation policies and their impact on improving national literacy, with a special focus on health polytechnics within the Ministry of Health. Library accreditation policies play a strategic role in ensuring the quality of library services that can support the development of public literacy as part of efforts to achieve national development goals. By the National Library Standards Policy set by the National Library of the Republic of Indonesia, library accreditation is a means of assessing the adequacy of library management against these standards, which is expected to improve the quality and access of services. The study highlights the challenges faced by health polytechnic libraries in meeting accreditation standards, including limited budgets, limited human resources, and limited policy support. In addition, this study explores the impact of accreditation policies on service quality, user engagement, and the role of libraries in improving public literacy, especially in the health sector. A descriptive qualitative research approach was used to gain an in-depth understanding of the implementation of this policy. The results of this study indicate that although most health polytechnic libraries are accredited, there are still obstacles in optimizing services and achieving literacy standards. This study provides recommendations to strengthen the library accreditation system by considering more supportive policies and improving the quality and accessibility of library services as a trusted literacy center in the community, especially in the context of health education.